Մ. Աբեղյանի անվան գրականության ինստիտուտ - Ավետիք Իսահակյան; Վարդան Դևրիկյան (Հայկական ՍՍՀ գիտությունների ակադեմիա)
Институт литературы имени М. Абегяна НАН РА – один из старейших институтов Армении. Он был основан в том же году, что и Академия наук Армении, в 1943 г. В состав Института входят следующие научные отделы: древней и средневековой армянской литературы, новой и новейшей армянской литературы, литературы армянской диаспоры, теории литературы, зарубежной литературы, текстологии и источниковедения, а также научной группы по изучению жизни и творчества Ов. Туманяна. M. Abeghyan Institute of Literature of NAS RA is one of the earliest Institutes of Armenia. It was established in 1943, along with Armenia’s Academy of Sciences. The Institute has the following scientific departments: Ancient and Medieval Armenian Literature, Modern and Contemporary Armenian Literature, Literature of the Armenian Diaspora, Theory of Literature, Foreign Literature, Studies of Texts and Sources, as well as a research team on the life and legacy of Hovhannes Toumanyan.
Keywords: History; Literature; Language and Literature; D History